2016
DOI: 10.1039/c6cp02544g
|View full text |Cite
|
Sign up to set email alerts
|

Chemical bonding and dynamic fluxionality of a B15+cluster: a nanoscale double-axle tank tread

Abstract: A planar, elongated B15(+) cationic cluster is shown to be structurally fluxional and functions as a nanoscale tank tread on the basis of electronic structure calculations, bonding analyses, and molecular dynamics simulations. The outer B11 peripheral ring behaves like a flexible chain gliding around an inner B4 rhombus core, almost freely at the temperature of 500 K. The rotational energy barrier is only 1.37 kcal mol(-1) (0.06 eV) at the PBE0/6-311+G* level, further refined to 1.66 kcal mol(-1) (0.07 eV) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
48
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 34 publications
2
48
0
Order By: Relevance
“…The multifold π/σ delocalization also supports unique dynamic structural fluxionality in boron‐based molecular systems. Since 2011, boron‐based molecular Wankel motors, nanoscale tank treads, molecular compass and propellers, and sandwich‐shaped binary clusters with dual‐mode dynamic fluxionality were reported; the latter mimics the revolution/rotation dynamics of the earth‐moon system at the subnanoscale. While studying dynamical fluxionality, the Zhai group also serendipitously encountered the first boron‐based helix clusters, Be 6 B 10 2− ( 1 , C 1 , 1 A) and Be 6 B 11 − ( 2 , C 2 , 1 A), which compete closely in energy with their three‐layered sandwich counterparts: Be 6 B 10 2− ( 3 , C 2v , 1 A 1 ) and Be 6 B 11 − ( 4 , C 2v , 1 A 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multifold π/σ delocalization also supports unique dynamic structural fluxionality in boron‐based molecular systems. Since 2011, boron‐based molecular Wankel motors, nanoscale tank treads, molecular compass and propellers, and sandwich‐shaped binary clusters with dual‐mode dynamic fluxionality were reported; the latter mimics the revolution/rotation dynamics of the earth‐moon system at the subnanoscale. While studying dynamical fluxionality, the Zhai group also serendipitously encountered the first boron‐based helix clusters, Be 6 B 10 2− ( 1 , C 1 , 1 A) and Be 6 B 11 − ( 2 , C 2 , 1 A), which compete closely in energy with their three‐layered sandwich counterparts: Be 6 B 10 2− ( 3 , C 2v , 1 A 1 ) and Be 6 B 11 − ( 4 , C 2v , 1 A 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The multifold π/σ delocalization also supports unique dynamic structural fluxionality in boron-based molecular systems. Since 2011, boron-based molecular Wankel motors, nanoscale tank treads, molecular compass and propellers, and sandwich-shaped binary clusters with dual-mode dynamic fluxionality were reported; [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] the latter mimics the revolution/ rotation dynamics of the earth-moon system at the subnanoscale. While studying dynamical fluxionality, the Zhai group [34,35] also serendipitously encountered the first boron-based helix clusters, Be 6 B 10…”
Section: Introductionmentioning
confidence: 99%
“…Boron-based nanoclusters are af ertile ground for unique quasi-planar (2D) structures up to 40 atoms, [1][2][3][4][5][6] extreme coordination environments, [1] and intriguing dynamic properties; [7][8][9][10][11][12][13][14][15][16][17] all these phenomena are attributed to the electron deficiencyo fb oron. During the past decades,n anomachines (including molecular rotors) [18] have emerged as ahot topic in chemistry and nanoscience.Aspectroscopic study of Zhai, Wang, and Boldyrev in 2010 on a2Dwheel-like B 19 À cluster [4] sparked an immediate proposal of molecular Wankel motor by Merino,Heine,and co-workers, [7] which was subsequently extended to aseries of circular clusters:B 13 + ,B 18 2À ,B 20 2À ,and B 12 Ir À .…”
mentioning
confidence: 99%
“…[15,16] Quite recently,a ll the predictions have made sense in view of the observation of fluxionality of B 13 + via cryogenic ion vibrational spectroscopy. [15,16] Quite recently,a ll the predictions have made sense in view of the observation of fluxionality of B 13 + via cryogenic ion vibrational spectroscopy.…”
mentioning
confidence: 99%
“…They found that interior holes or vacancies are only seen in the ground state when you reach a minimum size of B 20 − . Wang et al observed dynamic fluxionality in a B 15 + cluster, and they labeled this a nanoscale double-axle tank tread [15]. Borospherene (B 40 ) is predicted to act as a support-free spherical two-dimensional liquid at moderate temperatures [16].…”
Section: Introductionmentioning
confidence: 99%